PENINGKATAN KETERAMPILAN MEMBACA CEPAT DENGAN MENGGUNAKAN STRATEGI QUANTUM READING PADA SISWA KELAS V SDIT AL AKHYAR KABUPATEN BUNGO - Reni Guswita; Aprizan Aprizan; Subhanadri Subhanadri (Jurnal Muara Pendidikan, 2022)
Reading is one of the most important skills to be taught in elementary school. Quantum Reading Strategy is an alternative that can be used to improve students' reading comprehension. The purpose of this research is to describe the implementation of Quantum Reading strategy in improving reading comprehension skills during pre-reading, reading-reading and post-reading in grade V SDIT Al-Akhyar Muara Bungo. This research is classroom action research with four stages of planning, implementation, observation and reflection. The results of data analysis show that the use of Quantum Reading strategy can improve students' reading comprehension skills at the pre-reading, while-reading and post-reading stages in class V SDIT Al-Akhyar Muara Bungo.